Androgen deprivation therapy plus docetaxel and estramustine versus androgen deprivation therapy alone for high-risk localised prostate cancer (GETUG 12): a phase 3 randomised controlled trial. Issue 7 (July 2015) - Fizazi, Karim; Faivre, Laura; Lesaunier, François; Delva, Remy; Gravis, Gwenaëlle; Rolland, Frédéric; Priou, Frank; Ferrero, Jean-Marc; Houede, Nadine; Mourey, Loïc; Theodore, Christine; Krakowski, Ivan; et al.
Summary Background Early risk-stratified chemotherapy is a standard treatment for breast, colorectal, and lung cancers, but not for high-risk localised prostate cancer. Combined docetaxel and estramustine improves survival in patients with castration-resistant prostate cancer. We assessed the effects of combined docetaxel and estramustine on relapse in patients with high-risk localised prostate cancer. Methods We did this randomised phase 3 trial at 26 hospitals in France. We enrolled patients with treatment-naive prostate cancer and at least one risk factor (ie, stage T3–T4 disease, Gleason score of ≥8, prostate-specific antigen concentration >20 ng/mL, or pathological node-positive). All patients underwent a staging pelvic lymph node dissection. Patients were randomly assigned (1:1) to either androgen deprivation therapy (ADT; goserelin 10·8 mg every 3 months for 3 years) plus four cycles of docetaxel on day 2 at a dose of 70 mg/m2 and estramustine 10 mg/kg per day on days 1–5, every 3 weeks, or ADT only. The randomisation was done centrally by computer, stratified by risk factor. Local treatment was administered at 3 months. Neither patients nor investigators were masked to treatment allocation. The primary endpoint was relapse-free survival in the intention-to-treat population. Follow-up for other endpoints is ongoing. This study is registered with ClinicalTrials.gov, number NCT00055731. Findings We randomly assigned 207 patients to the ADT plus docetaxel and estramustine group and 206 to the ADT only group. Median follow-up was 8·8 years (IQR 8·1–9·7). 88 (43%) of 207 patients in the ADT plus docetaxel and estramustine group had an event (relapse or death) versus 111 (54%) of 206 in the ADT only group. 8-year relapse-free survival was 62% (95% CI 55–69) in the ADT plus docetaxel and estramustine group versus 50% (44–57) in the ADT only group (adjusted hazard ratio [HR] 0·71, 95% CI 0·54–0·94, p=0·017). Of patients who were treated with radiotherapy and had data available, 31 (21%) of 151 in the ADT plus docetaxel and estramustine group versus 26 (18%) of 143 in the ADT only group reported a grade 2 or higher long-term side-effect (p=0·61). We recorded no excess second cancers (26 [13%] of 207 vs 22 [11%] of 206; p=0·57), and there were no treatment-related deaths. Interpretation Docetaxel-based chemotherapy improves relapse-free survival in patients with high-risk localised prostate cancer. Longer follow-up is needed to assess whether this benefit translates into improved metastasis-free survival and overall survival. Funding Ligue Contre le Cancer, Sanofi-Aventis, AstraZeneca, Institut National du Cancer.